Subungual frictional hematoma due to overriding toe - Chang Patricia (Our Dermatology Online, 2011)
We report a male patient of 77 years with subungual frictional hematoma secondary to the deformity of his toe (overriding toe), this finding was incidental during his examination due to the presence of seborrheic keratosis on the scalp.Subungual hematomas of the nails are common it could be cause by major and minor trauma predominantly on the big toe, the different toe deformity predispose to have subungual frictional hematoma like in the present clinical case.